2001
DOI: 10.1038/ng720
|View full text |Cite
|
Sign up to set email alerts
|

CARD15 mutations in Blau syndrome

Abstract: We have identified three missense mutations in the nucleotide-binding domain (NBD) of CARD15/NOD2 in four French and German families with Blau syndrome. Our findings indicate that, in addition to Crohn disease, CARD15 is involved in the susceptibility to a second granulomatous disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
563
0
17

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 871 publications
(589 citation statements)
references
References 7 publications
9
563
0
17
Order By: Relevance
“…During the course of our analyses of CARD15, a report by Miceli-Richard et al described the detection of the same 2 variants that we observed, in 3 small European families with Blau syndrome (18). These families expressed classic Blau syndrome, without additional granulomatous lesions in other organ systems.…”
Section: Discussionsupporting
confidence: 77%
“…During the course of our analyses of CARD15, a report by Miceli-Richard et al described the detection of the same 2 variants that we observed, in 3 small European families with Blau syndrome (18). These families expressed classic Blau syndrome, without additional granulomatous lesions in other organ systems.…”
Section: Discussionsupporting
confidence: 77%
“…[152][153][154] Lossof-function mutations in NOD2 are associated with greatly increased susceptibility to Crohn's disease, [155][156][157] whereas gain-of-function mutations are linked to early onset sarcoidosis and Blau syndrome. 158,159 NOD2 contains an N-terminal CARD domain, a central NACHT region and C-terminal LRRs. 160 Upon binding of MDP to the LRRs of NOD2, the NACHT regions are exposed, allowing for self-oligomerization of NOD2 molecules, followed by homotypic interactions between the CARD domains of NOD2 and RIP2 161,162 (Figure 4).…”
Section: Rip2 and Nod Signallingmentioning
confidence: 99%
“…63 Recurrent mutations in the central NACHT domain from NOD2 have been linked with these diseases. 109 Compared to wild-type NOD2, the most frequently found mutation, R334Q, leads to increased basal NF-kB activation, in the absence of ligand, 51 and further increased NF-kB activation upon MDP stimulation. 55 Noticeably, Crohn's disease and BS are both characterized by a granulomatosis disorder, but mutations in NOD2 associated with these diseases have opposite effects on the NF-kB activation.…”
Section: Nod2mentioning
confidence: 99%